Windows Server 2003: The Complete Reference - Ivens, Kathy (McGraw-Hill, 2011)
Understand the architecture of operating systems including Windows NT, Windows 2000, and Windows Server 2003. Configure computers, manage users, and design your Active Directory. Implement group policies, enterprise services, and disaster planning and recovery processes.